2011
DOI: 10.1016/j.vaccine.2011.01.074
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with the defined chlamydial secreted protein CPAF induces robust protection against female infertility following repeated genital chlamydial challenge

Abstract: We previously have shown the efficacy of recombinant (r) chlamydial protease-like activity factor (CPAF) vaccination against hydrosalpinx development following primary genital chlamydial challenge. In this study, we evaluated further the protection induced by rCPAF vaccination against infertility. Following primary challenge, fertility levels were not significantly different between the mock- and CPAF-vaccinated and Chlamydia alone challenged mice. However, following secondary genital chlamydial challenge, moc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…Bacterial burdens were monitored using vaginal swabs on indicated days post C. mur challenge and subsequent plating on Hela cell monolayers grown on culture coverslips 36 . Chlamydial inclusions were detected using an anti- Chlamydia genus specific murine monoclonal primary antibody and goat anti-mouse IgG secondary antibody conjugated to Cy3 plus Hoescht nuclear stain.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial burdens were monitored using vaginal swabs on indicated days post C. mur challenge and subsequent plating on Hela cell monolayers grown on culture coverslips 36 . Chlamydial inclusions were detected using an anti- Chlamydia genus specific murine monoclonal primary antibody and goat anti-mouse IgG secondary antibody conjugated to Cy3 plus Hoescht nuclear stain.…”
Section: Methodsmentioning
confidence: 99%
“…ong-lasting hydrosalpinx is a pathological hallmark of tubal factor infertility associated with Chlamydia trachomatis infection in women (1) and C. muridarum infection in female mice (2)(3)(4). The precise mechanism of Chlamydia-induced long-lasting hydrosalpinx remains unknown, although Chlamydia-triggered inflammatory responses have been hypothesized to contribute significantly to chlamydial pathogenesis (5,6).…”
mentioning
confidence: 99%
“…These have recently been reviewed by several groups (Cochrane et al, 2010;Farris & Morrison 2011;Hafner 2007;Hafner & McNeilly 2008;Lyons et al, 2006;Miyairi et al, 2010;Rank & Whittum-Hudson 2010). These animal models have proved invaluable in providing knowledge of many novel candidate antigens for a vaccine (Barker et al, 2008;McNeilly et al, 2007;Murthy AK et al, 2011;Murthy et al, 2009) as well as novel delivery vehicles (Xu et al, 2011) and delivery routes such as oral and transcutaneous immunization for protection of genital infections (Hickey et al, 2010;Hickey et al, 2009) and have investigated a myriad of potential adjuvants (reviewed in Cochrane et al, 2010;Farris and Morrison, 2011; and immune responses elicited following animal immunization trials (Cunningham et al, 2011;McNeilly et al, 2007;Patton et al, 1983). For example it has recently been reported that a Vibrio cholerae ghost (VCG) multisubunit chlamydial vaccine delivered to mice by the intramuscular route stimulated immune memory in these animals (Eko et al, 2011).…”
Section: Chlamydia and Vaccinesmentioning
confidence: 99%
“…The fact that CTD43 has been shown to reduce (1) chlamydial infectivity in the murine model and (2) to prime a CD4+Th1 response in over 60% of patients infected with genital serovars of C. trachomatis, means that this antigen could be a promising vaccine candidate for chlamydial genital tract infections. A third candidate antigen showing great promise particularly for prevention of infertility resulting from repeated infections with C. trachomatis is the recombinant chlamydial protease-like activity factor (rCPAF) (Murthy et al, 2011).This antigen has been reviewed as a potential vaccine candidate (Murthy et al, 2009) and has successfully induced a combination of neutralising antibodies and cell-mediated responses against genital chlamydial challenge in a murine model of genital chlamydial infection (Li et al, 2010). More recent studies have reported that mice vaccinated intranasally with rCPAF and the adjuvant CpG were significantly protected against infertility as seen by a reduction in hydrosaplinx in rCPAF+CpG vaccinated mice following a primary genital challenge with C. muridarum (Murthy et al,, 2011).…”
Section: Chlamydia and Vaccinesmentioning
confidence: 99%